Assessment for learning in higher education - Sambell, Kay.; McDowell, Liz.; Montgomery, Catherine, 1962- (Milton Park, Abingdon, Oxon [England] : Routledge, 2013)
'an invaluable guide for practitioners, quality assurors, university managers and students themselves who wish to better understand the importance of assessment for learning, and it will further scholarship in the field significantly.' -Professor Sally Brown Assessment for Learning in Higher Education is a practical guide to Assessment for Learning (AFL); a term that has become internationally accepted in Higher Education and features in the learning and teaching strategies of many universities. It is also mandated by official bodies such as QAA in the UK. Many staff in Higher Education are uncertain about how to implement AfL, especially in times of increasingly constrained resources and this vital new guide provides solutions that make best use of assessment as a tool for learning.This book provides an important and accessible blend of practical examples of AFL in a variety of subject areas. The authors present practical, often small-scale and eminently'do-able' ideas that will make its introduction achievable. It provides practical case examples both for new lecturers and more experienced staff who may be interested in embedding AfL principles and practice into their university teaching. AFL approaches go beyond minor adaptations to teaching practice, and signify a shift in the foundations of thinking about assessment. With this in mind there is guidance on the development of effective learning environments and communities through the use of: collaboration and dialogue authentic assessment formative assessment peer and self assessment student development for the long term innovative approaches to effective feedback . It provides helpful, realistic guidance backed up by relevant theory and is written in an accessible, jargon-free style, grounded in practical experience and brought to life via a wide range of illustrative examples and case studies.Assessment for Learning in Higher Education fills a vital gap in assessment literature and as AFL is increasingly on the Higher Education agenda, with the promotion of assessment as a tool for learning, this book will become an essential handbook to guide all academic practitioners'--
'Assessment for Learning in Higher Education is a practical guide to Assessment for Learning (AFL); a term that has become internationally accepted in Higher Education (HE) and features in the learning and teaching strategies of many universities, and is mandated by official bodies such as QAA in the UK. Many staff in HE are uncertain about how to implement AFL, especially in times of increasingly constrained resources, and this vital new guide provides low cost solutions that make best use of the essential new assessment tool. This book provides an important and accessible blend of practical examples of AFL in a variety of subject areas. AFL approaches require more than minor adaptations to teaching practice, but the authors present practical, often small-scale and eminently'do-able' ideas that will make its introduction achievable. It provides practical case examples both for new lecturers and more experienced staff who may be interested in embedding AFL principles and practice into their university teaching'--
Keywords: Education, Higher -- Evaluation -- Methodology; Universities and colleges -- Examinations